Self-perceived assessment skills of pre-service and in-service teachers - Hussaain Alkharusi, (penerbit ukm, 2011)
One of the main responsibilities of the teachers is assessing student learning. As Such without adequate skills in educational assessment, it is unlikely that teachers' assessment practices will yield desired outcomes of student learning using a descriptive survey research design that is cross-sectional in nature, the present study investigated differences between pre-service and in-service teachers self-perceived assessment skills as a function of gender. Using a convenience sampling method, participants were 180 pre-service teachers and 150 pre-service teachers from Oman. Using principal component analyses, a 47 item self-perceived assessment skills questionnaire was developed and used in the study.Using a 2X2 multivariate analysis of variance, results indicated significant gender differences between pre-service and in sercice teachers in the self perceived assessment skills in analyzing test results, constucting and administering tests,communicating assessment results using performance assessment and grading implications for professional preparation of teachers in educational assessment as well as recommendations for future research are discussed.